A revision of Nazeris. VI. On the fauna of East Yunnan, China (Coleoptera: Staphylinidae: Paederinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2014)
A recent field trip to eastern Yunnan (Southwest China), a region from where only one species of Nazeris Fauvel, 1873 had been known, yielded thirteen undescribed Nazeris species, eleven of which are described and illustrated: N. brevilobatus sp. n. (Dongchuan env.), N. virilis sp. n. (Wuding env.), N. constrictus sp. n. (Gejiu env.), N. claviger sp. n. (Gejiu env.), and N. discissus sp. n. (Pingbian env.) of the newly established N. brevilobatus group; N. lamellatus sp. n. (Pingbian env.) of the newly established N. lamellatus group; N. semifissus sp. n. (Pingbian env.) of the newly established N. semifissus group; N. fibulatus sp. n. (Kunming env.), N. bulbosus sp. n. (Kunming env.), N. clavilobatus sp. n. (Dongchuan env.), and N. conicus sp. n. (Xundian env.) of the N. cangicus group. Together with N. zhangi Watanabe & Xiao, 1993, the latter three species form a distinct lineage within the N. cangicus group. Two species remain unnamed, as they are represented exclusively by females. The general distribution of the genus in Yunnan and the individual distributions of the newly described species are mapped. Nazeris now includes a total of 233 described species (plus seven subspecies), 118 of which have been recorded from mainland China. The fauna of Yunnan currently comprises 45 described species.KeywordsColeoptera, Staphylinidae, Paederinae, Nazeris, Palaearctic region, China, Yunnan, taxonomy, new species, species groups, distribution maps, diversityNomenclatural Actsbrevilobatus Assing, 2014 (Nazeris), spec. n.bulbosus Assing, 2014 (Nazeris), spec. n.claviger Assing, 2014 (Nazeris), spec. n.clavilobatus Assing, 2014 (Nazeris), spec. n.conicus Assing, 2014 (Nazeris), spec. n.constrictus Assing, 2014 (Nazeris), spec. n.discissus Assing, 2014 (Nazeris), spec. n.fibulatus Assing, 2014 (Nazeris), spec. n.lamellatus Assing, 2014 (Nazeris), spec. n.semifissus Assing, 2014 (Nazeris), spec. n.virilis Assing, 2014 (Nazeris), spec. n.